Comparison of Pregnancy Exercise Modifications in Improving the Functional Capability of Pregnant Women (JURNAL PROTEKSI KESEHATAN, 2024)
Hormonal changes in pregnant women result decreased muscle elasticity and flexibility, changes in static posture. Lower back pain in pregnant women can hinder daily functional activities. To find out physiotherapy interventions that can improve the functional abilities of pregnant women in conditions of low back pain. This research design uses randomized pre and post group design. This research used 20 subjects, divided into 2 groups. Analytical tests used paired sample t-test and independent sample t-test. Functional ability was measured using Pain Disability Index. Results of the analysis mean difference are p